1989
DOI: 10.1002/hep.1840090306
|View full text |Cite
|
Sign up to set email alerts
|

Urea cycle enzyme activities are normal and inducible by a high-protein diet in CCl4 cirrhosis of rats

Abstract: We produced moderately severe, inactive micronodular cirrhosis in rats using CCl4 and measured the urea cycle enzyme activities in liver after feeding a 15% casein diet for 1 week and again after a 60% casein diet for 1 week. There was no deficiency of any of the five urea cycle enzymes in cirrhotic livers of rats pair-fed the 15% casein diet. Argininosuccinate synthetase and carbamyl phosphate synthetase activities were lower than in non-pair-fed controls by some baselines. All five enzymes in cirrhotic liver… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

1989
1989
2011
2011

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(8 citation statements)
references
References 20 publications
0
8
0
Order By: Relevance
“…Further clinical (ascites), morphometric (liver weight/body weight ratio) or biological (transaminases, alcalin phosphatases) data is discrepant or lack ing [2, 6-12], For example, the liver weight/ body weight ratio varies from 20 to 60%, ascites is present in 0-90% of the rats and the increase in plasma transaminases varies con siderably from one study to another. Studies about nutritional status have been very lim ited [7] and only in a few of these instances have pair-fed controls [13] been used. Since cirrhosis induces anorexia [14] it is very diffi cult to draw conclusions from studies without pair-fed controls.…”
Section: Introductionmentioning
confidence: 99%
“…Further clinical (ascites), morphometric (liver weight/body weight ratio) or biological (transaminases, alcalin phosphatases) data is discrepant or lack ing [2, 6-12], For example, the liver weight/ body weight ratio varies from 20 to 60%, ascites is present in 0-90% of the rats and the increase in plasma transaminases varies con siderably from one study to another. Studies about nutritional status have been very lim ited [7] and only in a few of these instances have pair-fed controls [13] been used. Since cirrhosis induces anorexia [14] it is very diffi cult to draw conclusions from studies without pair-fed controls.…”
Section: Introductionmentioning
confidence: 99%
“…For the most frequently used animal model, the CCL,-induced cirrhosis of rats, however, the relationship between hyperammonemia and the capacity of the urea cycle is less clear. While a persistent decrease in the capacity of urea-N synthesis was noted by Fischer-Nielsen et al (9) and a deficient arginine synthetase system was found under somewhat different conditions (lo), Snodgrass reported normal activities of the urea cycle enzymes (11). Recently, alterations of liver glutamine metabolism were also taken into account.…”
mentioning
confidence: 96%
“…As an animal model for liver cirrhosis, the CCl 4 -induced model is the most frequently used one [13]. In this model, Snodgrass [17] and Gebhardt and Reichen [13] reported only a slight to moderate reduction of some of the urea cycle enzymes, and Gebhardt and Reichen [13] showed no correlation of serum ammonia concentration to liver CPS 1 activity in this model; however, they found a significant reduction of glutamine synthetase activity and a clear inverse correlation of its activity and serum ammonia concentration. Based on these results, they concluded that the drastic reduction in the activity of glutamine synthetase, rather than the decrease of the urea cycle enzymes, contributed significantly to the increase of blood ammonia concentrations that was characteristic for the cirrhotic animal.…”
Section: Discussionmentioning
confidence: 99%